2020
DOI: 10.1007/s11032-020-01132-w
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of three soybean landraces resistant to Asian soybean rust disease

Abstract: Phakopsora pachyrhizi is an obligatory biotrophic fungus that causes Asian soybean rust (ASR) disease. ASR control primarily involves chemical control and the use of resistant soybean cultivars carrying an Rpp (resistance to P. pachyrhizi) gene. This study aimed to characterize the ASR resistance of three soybean Asian landraces. By screening the world core collection (WC) of soybean, which consists of 80 varieties, three landraces were identified in Southeast Asia as resistant to ASR. Genetic mapping using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…The PI 594723 presented strong resistance, while the PI 200492 was classi ed as being weakly resistant (RB3 lesion type). Aoyagi et al (2020) observed susceptibility of PI 200492 against Brazilian ASR. Therefore, the PI 587880A showed less sporulation to ASR isolates, corroborating the present study results.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The PI 594723 presented strong resistance, while the PI 200492 was classi ed as being weakly resistant (RB3 lesion type). Aoyagi et al (2020) observed susceptibility of PI 200492 against Brazilian ASR. Therefore, the PI 587880A showed less sporulation to ASR isolates, corroborating the present study results.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the PI 587880A showed less sporulation to ASR isolates, corroborating the present study results. Aoyagi et al (2020) reported clear differences in the ASR reactions from genotypes carrying Rpp1 and Rpp1-b, and also among sources of Rpp1 such as PI 587886, Himeshirazu, and PI 200492, showing infection reactions of susceptibility, high resistance, and immunity respectively to the same isolate. Hossain et al (2015) and Akamatsu et al (2017) corroborate these differences in reactions to different isolates between accessions with the Rpp1 locus and genotypes with Rpp1-b.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations